Central and Eastern Europe : New Member States (NMS) Policy Forum, 2014, Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues Paper's objective is to illustrate economic benefits and costs from euro adoption by reviewing the main arguments and empirical evidence in Central and Eastern Europe: New Member States (NMS). The parameters of the euro adoption debate have shifted. Although countries joining the euro area in the 2000s could expect to benefit from a significant country risk premium, this premium has mostly vanished with the euro crisis. The NMS that have maintained exchange rate flexibility and monetary policy autonomy have, in general, made good use of it. During convergence, nominal currency appreciation supported more balanced growth and restrained credit and asset price booms. It is an open question whether the macroeconomic volatility of the past decade will recur. If divergent growth patterns and volatility were to repeat, euro adoption would constrain macro-policy options, especially for economies with large income gaps and asynchronized business cycles vis-a-vis the euro area. Thus, a large burden would be placed on other policy instruments to safeguard balanced growth, notably counter-cyclical fiscal policy and macro-prudential policies. Structural reforms to boost growth potential and facilitate internal adjustment would also be important.